Analisis Prinsip Kepemimpinan Pendidikan di Sekolah Menengah Kejuruan - Dessi Asdrayany; Anis Zohriah; Anis Fauzi (Departement of Mathematics Education, 2023)
This research uses a type of qualitative research with a library research approach by digging up information through the literature regarding leadership and education to answer the focus of the study in this study. This study examines the definition of educational leadership, general principles of educational leadership, general principles of educational leadership, educational leadership requirements, educational leadership skills, and educational leadership measurement instruments. Perinsip is one of the important things that must be owned by a leader. Principles can be a provision so that leadership can run well. Principles of educational leadership. among others: 1) constructive. 2) creative. 3) participatory. 4) Cooperative. 5) delegate. 6) integrative. 7) rational. 8) pragmatic. 9) do not force yourself to carry out activities beyond the capabilities of the madrasa. 10) exemplary. 11) adaptable and flexible.